La Conférence de l’Entente balkanique à Bucarest (20-22 février 1939) : le chant du cygne d’une tentative de confédération - Alkisti Sofou (Cahiers Balkaniques)
The Balkan Entente also called Balkan Pact was signed in Athens (February 9, 1934) between Rumania, Greece, Yugoslavia and Turkey. The member States aimed at defending their territorial status quo defined by the peace Treaty of Paris against attack by Bulgaria or Albania. They also aspired to strengthen their security towards the Italian maximalism and the hitlerian eastward expansion. The Conference in Bucharest is the second last. The Balkan Pact became defunct in 1940. Here we propose to examine the reasons of its dissolution. We shall focus on the aspects of the interbalkan relations and the parameters of British and French foreign policy. Thus, we will rehearse articles of the Greek, Rumanian, French and Turkish press as well as the testimonies of the two protagonists: Grigore Gafencu and Ioannis Metaxas.